Making inferences about elections and public opinion using incidentally collected data - Mellon, J (Routledge, 2017)
This handbook details the key developments and state of the art research across elections, voting behavior and the public opinion by providing both an advanced overview of each core area and engaging in debate about the relative merits of differing approaches in a comprehensive and accessible way. Bringing geographical scope and depth, with comparative chapters that draw on material from across the globe, it will be a key reference point both for advanced level students and researchers developing knowledge and producing new material in these sub-fields and beyond.